The arc of a covenant : the United States, Israel, and the fate of the Jewish people - Mead, Walter Russell (Alfred A. Knopf, 2022)
"A groundbreaking work that overturns the conventional understanding of the Israeli-American relationship and, in doing so, explores how fundamental debates about American identity drive our country's foreign policy"--